Cultural Politics Around East Asian Cinema 1939-2018 - Sudo, Noriko and Tanikawa, Takeshi (Trans Pacific Press, 2020)
Examines the interdependent relationships between the film industry and the state in East Asia, treating films as political economic products, mixtures of government policy and industrial motives, rather than mere works of art or media commodities. -- -- Chapters examine the East Asian film industries from the 1930s to the 2010s, which pursued their own economic and political goals by cooperating, negotiating, and conflicting with states. Through studies of national film policies, film industry strategies, and cultural-political influences on audience receptivity, this book reveals how films are formed by the interaction of the state, the film companies and audiences.
https://katalog.adlr.link/Record/51-9781920901462